Old people's homes: the relatives' view. Issue 6882 (3rd April 1993) - Nicholson, M; White, D
Abstract : On 1 April new arrangements came into force for arranging and funding residential care for elderly people in Britain. From now on those who seem to need full time care will be assessed first by care managers employed by local authority social services departments. This may lead to admission to an old people's home or a nursing home. Local authorities have been told to consult both users and carers about such decisions. But what about relatives who have not actually been giving care directly? The Relatives Association was set up last year as a voluntary organisation for the relatives and friends of older people living in residential homes. Below, its vice president, Mavis Nicholson, a journalist and broadcaster whose mother died of Alzheimer's disease in a residential home last year, gives her personal view of being such a relative. And Dorothy White, the association's founder, explains what the future may hold for elderly residents and their relatives.